2021
DOI: 10.3390/rs13234828
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology, Mineralogy, and Geochronology of Mare Basalts and Non-Mare Materials around the Lunar Crisium Basin

Abstract: The Nectarian-aged Crisium basin exhibits an extremely thin crust and complicated lunar geological history. This large multi-ring impact basin is characterized by prolonged lunar volcanism ranging from the Imbrian age to the Eratosthenian period, forming the high-Ti mare unit, low-Ti mare basalts, and very low-Ti mare unit. We produced an updated geological map of the Crisium basin and defined four mare units (Im1: 3.74 Ga; Im2: 3.49 Ga; Im3: 3.56 Ga; EIm: 2.49 Ga) in terms of distinct composition and mineralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The CSFD is a prevalent method employed for estimating the absolute model age (AMA) of lunar surfaces and other planetary bodies [72]. This method is based on radioisotopic age data from lunar samples and involves the establishment of a function to infer the ages of planetary surface units.…”
Section: Topographical and Geochronological Analysesmentioning
confidence: 99%
“…The CSFD is a prevalent method employed for estimating the absolute model age (AMA) of lunar surfaces and other planetary bodies [72]. This method is based on radioisotopic age data from lunar samples and involves the establishment of a function to infer the ages of planetary surface units.…”
Section: Topographical and Geochronological Analysesmentioning
confidence: 99%
“…1). According to the distribution characteristics of the composition of Mare Crisium, the geological units have been analyzed in previous studies [11], [12]. Former research has indicated that Imbrianaged and Eratosthenian-aged basalts are widely distributed within the basin.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Former research has indicated that Imbrianaged and Eratosthenian-aged basalts are widely distributed within the basin. Mare Crisium is essential basin for studying the lunar composition and magma evolution [12]. Based on LP-MAG data, Baek et al [6] discovered two magnetic anomaly areas.…”
Section: Geological Backgroundmentioning
confidence: 99%